Accelerating Sustainability Competencies in the Younger Generation through the Problem-Based Gamification Learning Model - Rima Meilita Sari; Ayu Suciani; Zukya Rona Islami; Ridhwan Ridhwan; Nabila Huwaida Sijabat; Ravinesh Rohit Prasad (Universitas Negeri Medan, 2026)
Higher education faces the challenge of shaping a young generation that cares about the environment. However, in reality, young people still face difficulties in developing sustainable skills. Problem-Based Game-Based Learning (PBGL) is learning innovation for shaping sustainable competencies. The aims of this study were to determine students' sustainable competencies, determine the effect of length of study on sustainable competencies, and analyse the effect of the PBGL model on sustainable competencies. To analyse the influence of PBGL, a pretest-posttest quasi-experimental design with a control group was used. Meanwhile, to determine the differences in sustainability competencies based on length of study, the Mann-Whitney U test was used. The instrument used was modified from the sustainability competency instrument to suit the characteristics of the research subjects. The results show that sustainability competencies before treatment were at a moderate level. After treatment, the experimental group showed an increase in holistic thinking to 90.5%, followed by an increase in conflict resolution to 95.37%. The experimental group showed a significant increase (t=13.462, p<0.001) with an increase in competence exceeding that of the control group. When viewed from the difference in length of study, there is a significant difference between fifth-semester and seventh-semester students. Seventh-semester students demonstrate higher competence than fifth-semester students (p<0.05). The difference in average shows a 10% difference. This indicates that academic maturity affects the effectiveness of PBGL and sustainability competence. The results show that the PBGL model is able to accelerate the development of sustainability competencies. This study has important theoretical and practical implications for the improvement of sustainable environmental curricula and higher education learning.